Methylation and its role in the disposition of tanshinol, a cardiovascular carboxylic catechol from Salvia miltiorrhizaroots (Danshen) - Tian Dan-dan; Jia Wei-wei; Liu Xin-wei; Wang Dan-dan; Liu Jun-hua; Dong Jia-jia; Li Li; Du Fei-fei; Xu Fang; Wang Feng-qing; Sun Yan; Huang Yu-xing; et al. (Acta Pharmacologica Sinica; Vol 36, No 5 (May 2015): Acta Pharmacologica Sinica, 2017)
Aim: Tanshinol is an important catechol in the antianginal herb Salvia miltiorrhiza roots (Danshen). This study aimed to characterize tanshinol methylation. Methods: Metabolites of tanshinol were analyzed by liquid chromatography/mass spectrometry. Metabolism was assessed in vitro with rat and human enzymes. The major metabolites were synthesized for studying their interactions with drug metabolizing enzymes and transporters and their vasodilatory properties. Dose-related tanshinol methylation and its influences on tanshinol pharmacokinetics were also studied in rats. Results: Methylation, preferentially in the 3-hydroxyl group, was the major metabolic pathway of tanshinol. In rats, tanshinol also underwent considerable 3-O-sulfation, which appeared to be poor in human liver. These metabolites were mainly eliminated viarenal excretion, which involved tubular secretion mainly by organic anion transporter (OAT) 1. The methylated metabolites had no vasodilatory activity. Entacapone-impaired methylation did not considerably increase systemic exposure to tanshinol in rats. The saturation of tanshinol methylation in rat liver could be predicted from the Michaelis constant of tanshinol for catechol-O-methyltransferase (COMT). Tanshinol had low affinity for human COMT and OATs; its methylated metabolites also had low affinity for the transporters. Tanshinol and its major human metabolite (3-O-methyltanshinol) exhibited negligible inhibitory activities against human cytochrome P450 enzymes, organic anion transporting polypeptides 1B1/1B3, multidrug resistance protein 1, multidrug resistance-associated protein 2, and breast cancer resistance protein. Conclusion: Tanshinol is mainly metabolized via methylation. Tanshinol and its major human metabolite have low potential for pharmacokinetic interactions with synthetic antianginal agents. This study will help define the risk of hyperhomocysteinemia related to tanshinol methylation.